The Colwyn Committee and the Incidence of Income Tax - Snavely, Tipton R. (Quarterly Journal of Economics, 1928)
I. Introductory: the Committee's work as a whole, 641. — II. Testimony of business men that a general income tax is added to prices, 643. — Refutation by economists, 645. — Statistical analysis by W. H. Coates of the Inland Revenue Department, 647. — III. Assumptions based on some special relation between cost of production and price, 651. — Absolute statement of marginal cost theory erroneous, 652. — Criticisms of Mr. Robertson examined, 657. — IV. Subsidiary arguments: (1) Relation to quantity theory of money; (2) At what rate does a progressive income tax become a part of costs? (3) Dilemma in relation to foreign trade, 662. — V. Distinction between incidence of an income tax and a commodity tax sustained, 666. — Indirect influences on price, 667.